An Introduction to operating systems - Deitel, Harvey M. (Addison-Wesley, 1990)
Presents general principles of operating systems and provides coverage of most important real systems in the market place. Three themes covered: paralell processing, distributed systems and open systems. Examines operating systems that run in multiprocessing environments and covers distributed computing in the context of open systems interconnection (OSI) standards and protocols.